2020
DOI: 10.3928/01484834-20200323-08
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Circle to Improve Nursing Clinical Judgment in an Undergraduate Nursing Program

Abstract: Background: Clinical judgment combines both decision making capacity and the ability to think critically. In an effort to foster clinical judgment in students, a quality improvement plan was initiated. Method: A teaching circle was created by key nursing faculty. After a review of the literature, goals, objectives, and aims were articulated. Faculty development, through the use of “lunch and learn,” was delivered using webinars, discussion, and applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Clinical judgement is viewed as an essential skill for nurses (Cappelletti et al, 2014; Martin et al, 2020; Tanner, 2006). The concept of clinical judgement has evolved, rather than been discovered or invented; therefore, it is difficult to determine when clinical judgement was first recognised and used in nursing.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical judgement is viewed as an essential skill for nurses (Cappelletti et al, 2014; Martin et al, 2020; Tanner, 2006). The concept of clinical judgement has evolved, rather than been discovered or invented; therefore, it is difficult to determine when clinical judgement was first recognised and used in nursing.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional teaching mode is usually used in gastrointestinal surgery nursing intern teaching work, but the study found that the teaching mode is the knowledge, simple teacher centered, related disease knowledge, it's not interns become active, and professional theoretical knowledge to clinical practical ability transformation process is slow, makes the teaching theoretical knowledge and skills evaluation results often reach the ideal[ 16 , 17 ]. However, a large number of foreign studies show that CBL-SSL-TBL combined with training mode and students' self-assessment to take nursing interns as the main body, which stimulates their desire for independent exploration and learning, and greatly improves the final assessment results[ 18 , 19 ]. However, the results of this paper show that in the comparison between the two groups, the operation skills and theoretical knowledge scores of the observation group were higher than that of the control group, and the difference had statistical significance ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…New registered nurses face increasing challenges, including high nurse/patient ratios and an increase in chronic illnesses (Woda et al, 2019). Nursing students need to develop clinical judgment skills (Ashcraft et al, 2013; Martin et al, 2020; Yang et al, 2019) and it is essential that opportunities to do so are provided in undergraduate nursing programs (Dickison et al, 2019).…”
mentioning
confidence: 99%
“…Nursing students need to develop clinical judgment skills (Ashcraft et al, 2013;Martin et al, 2020;Yang et al, 2019) and it is essential that opportunities to do so are provided in undergraduate nursing programs (Dickison et al, 2019).…”
mentioning
confidence: 99%
See 1 more Smart Citation